Miracle at St. Andrews [large type] : a novel - Patterson, James, 1947-; De Jonge, Peter (Little, Brown and Company, 2019)
Seasoned pro golfer Travis McKinley is cruising toward a new season when he misses a putt on the 18th green. Just like that, he's down and out and off the Senior Tour, his career all but dead. Then Travis is visited by a mysterious stranger whose vision is clear: go back to the beginning. The very beginning. Taking his advice both literally and to heart, Travis and his family travel to their ancestral home--Scotland. In the place where golf was born, he's able to look beyond getting the round ball in the round hole. And when Travis steps onto the Old Course at St. Andrews, the magic of the game takes over.